Description of a new species of armored spider from Myanmar (Araneae: Tetrablemmidae) - Labarque, Facundo M.; Grismado, Cristian J. (Zootaxa, 2009)
The Tetrablemmidae is a family of small to very small haplogyne, ecribellate, three-clawed spiders characterized mainly by the complex pattern of abdominal scuta (with dorsal, lateral and ventral plates) which justifies their common name “armoured spiders” (Shear 1978, Lehtinen 1981, Jocqué & Dippenaar-Schoeman 2006). They have a dorsal shield of prosoma heavily sclerotized, usually with rugous, pitted or reticulated surface, distinctly modified in the males of many genera. They lack direct eyes (anterior median), and several genera may lack some or all of the indirect eyes as well. One of the recognized tribes, Tetrablemmini (subfamily Tetrablemminae), contains the type genus of the family: Tetrablemma O. Pickard-Cambridge typically known by having four eyes displaced posteriorly in males, which have a convex clypeus, sometimes with tubercles, and chelicerae with anterior horns (Figs 6, 8─9; Lehtinen 1981: 56; Tong & Li 2008; Burger 2008).